Automated ESR spectrometer for various applications - Ivanchenko, I.; Karelin, S.; Popenko, N. (Functional Materials, 2004)
The paper presents a З-cm automated ESR spectrometer providing measurements be done in the temperature range 4.2 to З00 K. The spectrometer is designed according to a standard scheme with a superhet SHF radiation receiver and magnetic field modulation. The software for the spectrometer is designed as a single program module guaranteeing performance of all types of experiments and based on the principles of structural program -ming and elements of object-oriented programming assuring mutual independence of algorithms and the possibility to expand the software support. Advantages of the spectrometer are illustrated taking investigations of characteristics of diluted magnetic semiconduc tors as an example. Preliminary investigations of both organic and inorganic substances that have been carried out on the spectrometer testify to possibilities of its effective applic a-tion not only in physics but also in medicine and biology. B статье описан автоматизированный ЭСР-спектрометр З-см диапазона, обеспечивающий проведение измерений в температурном диапазоне 4,2-300 K. Спектрометр построен по стандартной схеме с супергетеродинным приемником СВЧ излучения и модуляцией магнитного поля. Программное обеспечение для спектрометра разработано в форме единого модуля программ, гарантирующего выполнение всех типов экспериментов и основанного на принципах структурного программирования и элементов объектно-ориентированного программирования, обеспечивающего взаимную независимость алгоритмов и возможность расширения программной поддержки. Преимущества разработанного спектрометра показаны на примере исследования функций разбавленных магнитных полупроводников. Предварительные исследования как органических, так и неорганических веществ, выполненные с помощью данного спектрометра, свидетельствуют о возможности его эффективного применения не только в физике, но также в медицине и биологии. У статті представлений автоматизований ЕСР спектрометр. Спектрометр дозволяє проводити вимірювання в iнтервалi температур 4,2-300 К. ЕСР спектрометр створений за стандартною схемою із супергетеродинним НВЧ приймачем та модуляцією магнітного поля. Програмне забезпечення для ЕСР спектрометра розроблено у вигляді єдиного програмного модуля, який дозволяє проводити усі види експериментів. Його структура базується на принципах структурного програмування та елементах об’єктно-орієнтова-ного програмування, які забезпечують взаємну незалежність алгоритмів та можливість розширення програмного забезпечення. Переваги спектрометра продемонстровано на прикладі досліджень характеристик напівмагнітних напівпровідників. Проведені на спектрометрі попередні дослідження різноманітних речовин органічної та неорганічної природи свідчать про можливість його ефективного використання також у медицині та біології.